(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2020)
The main objective of information organization is to disseminate information objects effectively to users. It is a complex but important task that uses elements such as the form and informational content of documents, an d it is a prerequisite for an efficient organization. Research laboratories are examples of organizations that have a diverse and complex set of data that must be well organized. Their flow of information needs to be mapped to properly identify people, inf ormation sources, technology used as well as products and services. In this work we describe the development of the FluxP system to organize information on protocols from a Biology Research Laboratory — The Animal Venoms and Toxins Laboratory (LVTA) from the Federal University of Minas Gerais – Brazil. FluxP is able to manage protocol data and makes it simple to store and retrieve protocols to aid in the experimental work, increasing the reliability of experiments and helping reduce experimental errors. By establishing a central repository for protocols FluxP prevents protocols from being misplaced or lost and by categorizing them FluxP makes it simple to retrieve protocols based on keywords. The system is currently being used by LVTA to manage a collection of 50 protocols, and can be easily adapted for other laboratories Keywords: Information management.LIMS; Biology Laboratory.Research Protocols. Link: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/9174/6287